Enhancing Legislation to Combat "Transfer Pricing" for Foreign-Invested Enterprises in Vietnam - Nguyen, Thi Hoang Oanh (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
Since the enactment of the Law on Foreign Investment in Vietnam in 1987, the state has created favourable conditions for foreign investors to invest in Vietnam, bringing various benefits such as capital, technology, and employment opportunities. However, foreign investors, in their investment activities in Vietnam, have engaged in "transfer pricing," leading to revenue loss for the Vietnamese budget. Transfer pricing is not a new phenomenon in today's economic development; as early as 2012, certain FDI enterprises, like Coca-Cola, Pepsico, Adidas, and Metro, were suspected of engaging in transfer pricing due to continuous reported losses while expanding their business operations. Vietnam has gradually recognized and adjusted transfer pricing activities. Currently, the legal framework for combating transfer pricing is primarily stipulated in Decree 132/2020/ND-CP, which regulates tax management for enterprises with related-party transactions (hereinafter referred to as Decree 132/2020/NDCP). This article analyzes the nature of transfer pricing and its impact and proposes improvements to the relevant legal provisions on control “transfer pricing”.